Voice of a woman: influence of interaction partner characteristics on cycle dependent vocal changes in women - Janek S. Lobmaier; Wilhelm K. Klatt; Stefan R. Schweinberger; Stefan R. Schweinberger (Frontiers in Psychology)
IntroductionResearch has shown that women’s vocal characteristics change during the menstrual cycle. Further, evidence suggests that individuals alter their voices depending on the context, such as when speaking to a highly attractive person, or a person with a different social status. The present study aimed at investigating the degree to which women’s voices change depending on the vocal characteristics of the interaction partner, and how any such changes are modulated by the woman’s current menstrual cycle phase.MethodsForty-two naturally cycling women were recorded once during the late follicular phase (high fertility) and once during the luteal phase (low fertility) while reproducing utterances of men and women who were previously assessed to have either attractive or unattractive voices.ResultsPhonetic analyses revealed that women’s voices in response to speakers changed depending on their menstrual cycle phase (F0 variation, maximum F0, Centre of gravity) and depending on the stimulus speaker’s vocal attractiveness (HNR, Formants 1–3, Centre of gravity), and sex (Formant 2). Also, the vocal characteristics differed when reproducing spoken sentences of the stimulus speakers compared to when they read out written sentences (minimum F0, Formants 2–4).DiscussionThese results provide further evidence that women alter their voice depending on the vocal characteristics of the interaction partner and that these changes are modulated by the menstrual cycle phase. Specifically, the present findings suggest that cyclic shifts on women’s voices may occur only in social contexts (i.e., when a putative interaction partner is involved).